Prebiotic competence of spirulina on the production performance of broiler chickens - Jamil, A. B. M. Rawshon; Akanda, Md. Rashedunnabi; Rahman, Md. Mahfujur; Hossain, Md. Anwar; Islam, Md. Siddiqul (Journal of Advanced Veterinary and Animal Research, 2015)
The study was conducted to evaluate the prebiotic effects of Spirulina as a growth and immunity promoter for broiler chickens. Birds (n=100) were randomly and equally distributed into four groups (T0, T1, T2 and T3) and fed on a diet containing 0, 2, 4 and 8 g Spirulina/kg feed respectively for 4 weeks. The body weight was significantly (P<0.05) increased in the treatment groups fed with Spirulina diet from 7th days to 28th days old. FCR was also significantly (P<0.05) decreased among the treatment groups. Hematological parameters were significantly (P<0.05) increased except ESR which was decreased significantly (P<0.05) in the treatment group. Aspartate aminotransferase (ALT) and alanine aminotransferase (AST) level were significantly (P<0.05) decreased in all the treatment groups. The study suggests that, Spirulina is a good natural feed additive which has a tremendous effect to improve the broiler production and thereby may reduce the production cost. http://dx.doi.org/10.5455/javar.2015.b94